Estimation of Chemical Compounds in Selected Italian and French Wines Produced through Organic and Conventional Methods - Alicja Ponder; Maciej Frąckowiak; Marcin Kruk; Ewelina Hallmann (Applied Sciences, 2024)
In this study, Italian and French wines produced through organic and conventional methods were analyzed. Three different varieties of wines were examined, including Cabernet Sauvignon, Merlot, and Syrah. Individual compounds were quantitatively and qualitatively analyzed to measure their levels of organic acids and polyphenols, such as phenolic acids, flavonoids, and anthocyanins, as well as their different chemical fractions. Among the French wines, organic varieties contained significantly higher levels of lactic and acetic acids, as well as catechins and rutin, compared to those of their conventional counterparts. Based on its chemical components, one of the best wines in this group was Syrah. In contrast, similar results were observed for the Italian wine produced by both systems. One type of Italian wine with superior results was Cabernet Sauvignon.